Changes in gene and genotype frequencies during the development of the grass carp Ctenopharyngodon idella - LiB. He; Lv Xiong; AiD. Zhang; YongM. Li; Rong Huang; LanJ. Liao; ZuoY. Zhu; YaP. Wang (Journal of Fish Biology, 2018)
In this study, a full‐sib population of Ctenopharyngodon idella was constructed and approximately 500 C. idella individuals were sampled at four early developmental stages (hatching, first feeding, juvenile fish and young fish). Four DNA pools were constructed and subjected to next‐generation sequencing. On the basis of the identification of single nucleotide polymorphisms (SNP), changes in gene and genotype frequencies during the developmental progress of C. idella were revealed, which indicates that death during the early developmental stage is not a random process. These findings will establish the basis for further studies performed for identifying superior alleles or genotypes as target markers for molecular breeding.

Continuous application of different organic additives can suppress tomato disease by inducing the healthy rhizospheric microbiota through alterations to the bulk soil microflora - Hongjun Liu; Wu Xiong; Ruifu Zhang; Xinnan Hang; Dongsheng Wang; Rong Li; Qirong Shen (Plant and Soil, 2018)